1985
DOI: 10.1007/bf02083507
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between haemodialysis anaemia and copper and zinc

Abstract: In fifteen chronic haemodialysis patients, serum and corpuscular copper and zinc concentrations were examined before and after dialysis. Serum copper levels were normal before dialysis and elevated after dialysis. However, corpuscular copper levels were low before dialysis and did not change after dialysis. Serum zinc concentrations before dialysis were low and significantly increased after dialysis. Corpuscular zinc levels before dialysis were high, but were unchanged after dialysis. There was a good correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Proteinuria in renal failure leads to excessive excretion of zinc (3) . On the other hand, the present study found that Zn level was significantly increased after dialysis, this results agrees with Hosokawa et al, in 1985 (9) , who found that serum zinc concentration increases `after dialysis.…”
Section: Discussionsupporting
confidence: 93%
“…Proteinuria in renal failure leads to excessive excretion of zinc (3) . On the other hand, the present study found that Zn level was significantly increased after dialysis, this results agrees with Hosokawa et al, in 1985 (9) , who found that serum zinc concentration increases `after dialysis.…”
Section: Discussionsupporting
confidence: 93%
“…The erythrocyte Zn concentration in patients with chronic renal failure (CRF) was reported to be low [8], normal (3 papers) [17], but more often increased [18,19,22,29]. High erythrocyte Zn in the presence of low plasma Zn in patients with renal failure is probably in relation to the activity of the major Zn-containing erythrocyte enzyme carbonic anhydrase.…”
Section: Zincmentioning
confidence: 99%
“…Previously, we and others reported that abnormalities of aluminum [1][2][3][4], silicon [5][6][7][8], zinc [9][10][11][12], manganese [13][14][15][16] and nickel [17][18][19][20] caused various kinds of compli cations in chronic hemodialysis (HD) patients. Elevated serum Al levels in chronic HD patients [1][2][3][4] were asso ciated with encephalopathy [3].…”
Section: Introductionmentioning
confidence: 99%